Health-interfering streets experiences: homeless people’s perspective - Valle, Fabiana Aparecida Almeida Lawall (2022)
Health , understood as a multidetermined state, expresses the political and social organization of a Country. From Brazilian 1988’s Federal Constitution, health has been understood as a individual right and a State duty. People living on streets exposes importante obstacles on the making of such a right. Objective: understand the difficulties of street’s experiences that interfere on the percepction and health state of adult individuals living on the streets of a municipality in Zona da Mata region on the State of Minas Gerais, Brazil. Qualitative methodological approach, through semi-structured interviews and observation versus registration on a field diary. Participated 20 people living on the streets. The highligthed difficulties were those related with enviroment and climate exposition, as rain and cold; prejudice; vulnerabiltity to physical and sexual abuse; obstacles to food, drinking water and toilets acess; difficulties to enter into some social spaces and to engage to health treatments. By knowing the situations that determine health levels among people living on the streets, it is possible to build politics and strategies to contemplate their real needs. Inter-sectoriality of public action is still a great challenge, nevertheless, necessary to accomplish the realization of a right wich is fundamental and universal: Health.